Ethnocentrism and its Effect on Preference of Indian Consumers for Foreign and Domestic Products (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The purpose of this study is to explore the  relationship between Indian consumers’  ethnocentric tendency (CET) and consequent  purchase behavior for domestic and foreign  products. This research paper examines the  relationships between CET and the behavioural  outcomes of Indian consumers. The proposed  hypotheses are tested for the CET-Consequent  Behaviour Framework using the results of  the survey of Indian consumers. Besides  descriptive statistics, correlation coefficient  and regression analysis were applied to examine  the relationship between CET and consequent  behavioural constructs. This study concludes  that a significant relationship exists between  consumer ethnocentrism and consequent  purchase behavior (overall general purchase  intention) for domestic and foreign products.  The study has its implication for the domestic  marketers as well as foreign marketers operating  in India. While domestic firms can overplay the  ethnocentric sentiments of Indian consumers in  marketing their products, foreign firms have to  plan peculiar entry and marketing strategies to  deal with such sentiments.
Keywords: Consumer ethnocentrism; Consequent buying behavior; Domestic products; Foreign products